(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
The educational project involving the design of a school yard using Google SketchUp, presented in this paper, was originally designed and implemented by undergraduate students at the Department of Primary Education of the National and Kapodistrian University of Athens (UoA) in the context of their studies in the Teaching Geography with ICT course. The aim of the project was to create awareness of spaces and their functions, and to redesign those spaces using Google Sketch up according to criteria relating both to the environment and the needs of pupils and their education. The assessment of this initiative, carried out by the undergraduate students during the pilot study showed that there is a distinct need for connecting real spaces with technology and for familiarity with the tools that help pupils visualise the space and that Google SketchUp could be an effective tool that is easily applied to this project and can enrich geography lessons for pupils in upper primary and lower secondary education.